Impossible decision? An investigation of risk trade-offs in the intensive care unit. Issue 1 (2nd January 2018) - Reader, Tom W.; Reddy, Geetha; Brett, Stephen J.
Abstract: In the intensive care unit (ICU), clinicians must often make risk trade-offs on patient care. For example, on deciding whether to discharge a patient before they have fully recovered in order to create a bed for another, sicker, patient. When misjudged, these decisions can negatively influence patient outcomes: yet it can be difficult, if not impossible, for clinicians to evaluate with certainty the safest course of action. Using a vignette-based interview methodology, a naturalistic decision-making approach was utilised to study this phenomena. The decision preferences of ICU clinicians ( n  = 24) for two common risk trade-off scenarios were investigated. Qualitative analysis revealed the sample of clinicians to reach different, and sometimes oppositional, decision preferences. These practice variations emerged from differing analyses of risk, how decisions were 'framed' (e.g. philosophies on care), past experiences, and perceptions of group and organisational norms. Implications for patient safety and clinical decision-making are discussed. Practitioner Summary: Physicians managing ICUs have to make rapid decisions with incomplete information and suboptimal resources. A qualitative vignette-based interview study examined how such decisions are made. We found physicians used a heterogeneous mixture of risk assessments, factual knowledge and prior experience to make judgements, which leads to potential for inconsistent decision-making.